Implmentasi Permenkumham Nomor 17 Tahun 2018 Tentang Pendaftaran Persekutuan Komanditer, Persekutuan Firma Dan Persekutuan Perdata Di Kota Yogyakarta - Hidayatus Sholehah (Officium Notarium, 2021)
This study discusses the formulation of problems related to the implementation of Permenkumham Number 17 of 2018 concerning Registration of Limited Partnerships, Firm Partnerships and Civil Partnerships in Yogyakarta City, and the obstacles it faces. This research includes a typology of empirical legal research. Research data in the form of primary data obtained by interviewing the object of research while secondary data was collected from literature study. The results of this study are that after the enactment of Permenkumham Number 17 of 2018, Yogyakarta City Notaries can carry out well and feel the benefits with the enactment of the Minister of Law and Human Rights Number 17 of 2018. Constraints that arise are, first, related to problems on the server or maintenance in the AHU Online menu; second, related to the age of Notaries who are difficult to adapt in implementing Permenkumham Number 17 of 2018.Keywords: Implementation; notary; registration of civil partnershipAbstrakPenelitian ini memaparkan rumusan masalah terkait implementasi Permenkumham Nomor 17 Tahun 2018 tentang Pendaftaran Persekutuan Komanditer, Persekutuan Firma dan Persekutuan Perdata di Kota Yogyakarta, dan kendala yang dihadapinya. Penelitian ini termasuk tipologi penelitian hukum empiris. Data penelitian berupa data primer didapat dengan cara wawancara dengan objek penelitian sedangkan data sekunder dikumpulkan dari studi pustaka. Hasil dari penelitian ini adalah bahwa pasca berlakunya Permenkumham Nomor 17 tahun 2018, Notaris Kota Yogyakarta dapat melaksanakan dengan baik dan merasakan manfaat dengan berlakunya Permenkumham Nomor 17 Tahun 2018 tersebut. Kendala yang muncul, pertama, terkait permasalahan di server atau perawatan dalam menu AHU Online; kedua, terkait usia Notaris yang sulit beradaptasi dalam menerapkan Permenkumham Nomor 17 Tahun 2018.Kata Kunci: Implementasi; notaris; pendaftaran persekutuan perdata